2024
DOI: 10.1111/ppl.14266
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multi‐omics analysis reveals the crucial biological pathways involved in the adaptive response to NaCl stress in peanut seedlings

Nan Zhang,
He Zhang,
Zhenghao Lv
et al.

Abstract: Plant growth is restricted by salt stress, which is a significant abiotic factor, particularly during the seedling stage. The aim of this study was to investigate the mechanisms underlying peanut adaptation to salt stress by transcriptomic and metabolomic analysis during the seedling stage. In this study, phenotypic variations of FH23 and NH5, two peanut varieties with contrasting tolerance to salt, changed obviously, with the strongest differences observed at 24 h. FH23 leaves wilted and the membrane system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Peanut can improve the adaptability to salt stress by regulating a series of secondary metabolic processes, and significantly affect the expression of core genes in the process of flavonoids biosynthesis, phenylpropanoid biosynthesis, starch and sugar metabolism, nitrogen metabolism, circadian rhythm and so on [ 42 ]. Previous studies on the metabolomic data of leaves from two peanut genotypes under salt stress have confirmed that trehalose-6-phosphate and D-trehalose are important differential metabolites, indicating that trehalose biosynthesis plays an active role in the response of peanut leaves to salt stress [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peanut can improve the adaptability to salt stress by regulating a series of secondary metabolic processes, and significantly affect the expression of core genes in the process of flavonoids biosynthesis, phenylpropanoid biosynthesis, starch and sugar metabolism, nitrogen metabolism, circadian rhythm and so on [ 42 ]. Previous studies on the metabolomic data of leaves from two peanut genotypes under salt stress have confirmed that trehalose-6-phosphate and D-trehalose are important differential metabolites, indicating that trehalose biosynthesis plays an active role in the response of peanut leaves to salt stress [ 43 ].…”
Section: Discussionmentioning
confidence: 99%